Web-based Educational Payment Information System using Role-based Access Control Security - Hidayatur Romadhan; Mansur Mansur (Universitas Islam Indragiri, 2026)
The management of Sumbangan Pembinaan Pendidikan (SPP) payments in Islamic boarding schools still faces issues related to delayed recording, data inaccuracies, and weak access control over financial information. This study aims to design and implement a web-based SPP payment information system that applies Role-Based Access Control (RBAC) to improve administrative order and data security. The system was developed using the Waterfall method, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The application was built using the Laravel framework with RBAC implemented at the middleware level to manage user access based on defined roles, namely Super Admin, Treasurer, Student Guardian, and Principal. System testing was conducted using the Black-Box Testing method to validate core functionalities, including user authentication, billing management, payment verification, report generation, and role-based access restrictions. The test results indicate that all system functions operate as expected and that the RBAC mechanism effectively prevents unauthorized access to sensitive features and data. Overall, the implemented system supports more structured payment administration, improves data accuracy, and enhances security and accountability in managing financial transactions within the pesantren environment.